Case Report: Staghorn Stone Successfully Treated With Open Nephrolithotomy - Ezra Harun Florentino Nababan; Ephram Sanders Alfian Siadary; Arley Sandra Telussa (Brawijaya Journal of Urology, 2023)
Objectives. Staghorn stones are large branching stones that fill part of all of the renal pelvis and renal calyces and they can be complete or partial depending on the level of occupancy of the collecting system. The case of this Staghorn Kidney Stone stone was reported at Leona hospital, Kupang, East Nusa Tenggara, Indonesia.Case. The patient is a 22 year old male with Staghorn renal stone with the size measured 14 x 11 cm. The patient came to the ER with complaints of low back pain and patient complains of difficulty urinating first. nephrolithotomy surgical procedure was performed to release the stone.Conclusion. The cause of the Renal staghorn stone should be considered prior to treatment as eliminating the cause and the underlying factor will reduce the complications and recurrence rates.